A systematic review of the operational definitions for antipsychotic response in delusional disorder. (September 2018) - González-Rodríguez, Alexandre; Estrada, Francesc; Monreal, José A.; Palao, Diego; Labad, Javier
Abstract : This review aimed to examine and analyse the definitions used for antipsychotic response in delusional disorder (DD) and to provide a discussion of the methodology used. A systematic review was performed using the PubMed, Scopus and PsycINFO databases (1990–October 2017) according to the PRISMA statement. In addition, reference searches were performed manually through identified studies to obtain other relevant articles. The search terms included 'antipsychotic response', 'antipsychotics', 'treatment response' and 'delusional disorder'. After the screening and selection processes, 11 studies fulfilled our inclusion criteria using different methods to define antipsychotic response in DD. Studies included chart reviews ( n =5) and observer-rated scales ( n =6), in which two studies used the Clinical Global Impression-Improvement scale, two studies evaluated antipsychotic response by mean changes from the baseline to endpoint scores [Positive and Negative Syndrome Scale (PANSS) and Brief Psychiatric Rating Scale], one study combined the Clinical Global Impression-Improvement scale and mean changes from baseline scores (PANSS) and one study reported responder rates on the basis of a scale-derived cut-off (PANSS). A lack of consensus in the definitions of antipsychotic response in DD and a high degree of heterogeneity of the methods used are reflected. Recent proposals on the use of scale-derived cut-offs to evaluate antipsychotic response in schizophrenia would be highly recommended for DD research.